Circadian disruption is associated with altered postural control in aged individuals under eye closed condition - Zhào, Hóngyi; Zhang, Zhiqiang; Bai, Yinxia; Li, Peng; Huang, Yonghua (Frontiers in Neuroscience, 2025)
BackgroundSleep loss is reported to affect postural control. However, the relationship between increased postural sway and the circadian rhythm (CR) remains unclear.ObjectivesTo assess performance in the postural control test in aged individuals with an abnormal CR.MethodsThis cross-sectional observational study included two groups of participants: those at high risk of falling (HFR) and those at low risk of falling (LFR), which was determined by the clinical cut-off score for the sway path with open eyes. Each participant wore an ActiGraph device on their non-dominant hand for 5–7 days. A non-parametric analysis of CR variables, including interdaily stability (IS), intraday variability (IV), relative amplitude (RA), interdaily coefficient of variation (ICV), etc., was used to evaluate the postural stability with a posturographic platform during a 30-s static balance test under the eyes closed (EC) and eyes open (EO) condition.ResultsIndividuals in the HFR group demonstrated significantly higher scores in the Downton fall risk index (DFRI), higher ICV, and lower IS and M10 activity counts than the LFR group. Linear regression analysis revealed that under the EO condition, there was no association between postural control and CR disruption; however, under the EC condition, L5 was positively associated with variables reflecting an increase in postural sway.ConclusionIncreased postural sway was found to be associated with CR disruption in aged adults under the EC condition.